2021
DOI: 10.21037/acs-2021-tviv-131
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic outcomes after valve-in-valve transcatheter aortic valve replacement: a single-center experience

Abstract: Background: Valve-in-valve transcatheter aortic valve replacement (ViV-TAVR) has emerged as a safe, effective alternative to redo aortic valve surgery in high-risk patients with degenerated surgical bioprosthetic valves. However, ViV-TAVR has been associated high postprocedural valvular gradients, compared with TAVR for native-valve aortic stenosis.Methods: We performed a retrospective study of all patients who underwent ViV-TAVR for a degenerated aortic valve bioprosthesis between January 1, 2013 and March 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Concluding procedural aspects and initial outcomes, it seems to be evident, that VIV-TAVR as a heterogeneous group consisting of different procedures (by means of combinations of surgical and TAVR valves) -with respect to some special cases -basically is safe and provides good or at least acceptable initial hemodynamic results [3,13,16]. Furthermore, it is evident, that VIV-TAVR in small surgical valves as well as stented valves is associated with higher postprocedural gradients [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Concluding procedural aspects and initial outcomes, it seems to be evident, that VIV-TAVR as a heterogeneous group consisting of different procedures (by means of combinations of surgical and TAVR valves) -with respect to some special cases -basically is safe and provides good or at least acceptable initial hemodynamic results [3,13,16]. Furthermore, it is evident, that VIV-TAVR in small surgical valves as well as stented valves is associated with higher postprocedural gradients [16].…”
Section: Discussionmentioning
confidence: 99%
“…If not, it must remain a bailout-option for risky patients. The presently available literature does not allow to answer this crucial question conclusively [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,13,16 Furthermore, it is evident, that VIV-TAVR in small surgical valves as well as stented valves is associated with higher postprocedural gradients. 16 As far as good-but Dvir et al 13 already identified a sore spot in the VIVID. Patients presenting with an internal diameter equal or less 20 mm of the surgical valve showed to have an inferior 1-year survival.…”
Section: Discussionmentioning
confidence: 99%